2015
DOI: 10.1002/pola.27579
|View full text |Cite
|
Sign up to set email alerts
|

Imino(phenoxide) compounds of magnesium: Synthesis, structural characterization, and polymerization studies

Abstract: A plethora of magnesium compounds containing imino(phenoxide) (1–4) and bis(imino)phenoxide (5–10) ligand backbone have been synthesized via the reaction of diethyl magnesium with two equivalent of the corresponding ligand. These compounds were completely characterized by different spectroscopic techniques and elemental analyses. The monomeric nature of the magnesium complexes 3, 5, 6, 9, and 10 were further confirmed by single crystal X‐ray diffraction studies. The magnesium centers posses distorted trigonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 164 publications
(228 reference statements)
0
17
0
Order By: Relevance
“…ROP processes offer excel control in terms of molecular weight ( M n ), polydispersity (MWDs) and microstructure . Several complexes have been successfully employed in the ROP of lactide, including lithium, sodium, potassium, magnesium, calcium, strontium, aluminum, tin, zinc, some transition metals, and rare‐earth metals . Since complete elimination of catalyst rests from the polymer is virtually impossible, it is highly preferable to use non‐ or low toxic metals (for instance for biomedical applications).…”
Section: Introductionmentioning
confidence: 99%
“…ROP processes offer excel control in terms of molecular weight ( M n ), polydispersity (MWDs) and microstructure . Several complexes have been successfully employed in the ROP of lactide, including lithium, sodium, potassium, magnesium, calcium, strontium, aluminum, tin, zinc, some transition metals, and rare‐earth metals . Since complete elimination of catalyst rests from the polymer is virtually impossible, it is highly preferable to use non‐ or low toxic metals (for instance for biomedical applications).…”
Section: Introductionmentioning
confidence: 99%
“…L1 and L2 were synthesized in high yields according to a modified literature procedure. [14][15][16][17]22 Complexes C1 and C2 ( Figure 1) were also obtained in high yields. The structures of these ligands allow the coordination of two zinc(II) centers while the vast majority of the phenoxy-imine ligands coordinate to only one metal.…”
Section: Ligands and Complexesmentioning
confidence: 94%
“…Yield: 62%; mp > 300 °C; elemental analysis for C 24 C1 was prepared using a modified literature procedure. [14][15][16][17] In a 25 mL Schlenk flask, 15% hexane solution of ZnEt 2 (0.20 mL, 0.22 mmol) was added dropwise to a solution of L1 (0.100 g, 0.11 mmol) in dry toluene (10 mL) at 0-4 °C (L1/ZnEt 2 molar ratio = 1:2). The reaction mixture was stirred overnight at room temperature.…”
Section: Synthesis Of L1mentioning
confidence: 99%
“…For example, Rood et al have prepared three (salicylaldiminato)magnesium complexes and studied the coordination environment around the magnesium center dependend on the local steric environment of the ligand . Subsequently, Chakraborty et al reported that similar imino(phenoxido)magnesium complexes were found to be active towards the controlled ring opening polymerization (ROP) of lactides and the copolymerization of carbon dioxide with cyclohexene oxide and styrene oxide …”
Section: Introductionmentioning
confidence: 99%